Η ηθική αποτίμηση της χρήσης απαγορευμένων ουσιών στον αθλητισμό σύμφωνα με τους φοιτητές του ΤΕΦΑΑ Πανεπιστημίου Αθηνών - Μαυροδάκος, Π.; Γογγάκη, Κ.; Πολυδωρόπουλος, Κ. (http://archive-gr.com/gr/p/pepfa.gr/2013-09-16_2866954-titles_6, 2011)
The moral evaluation of the use of illegal substances according to The students of the Sport Physical Education Department of the University of Athens. Panagiotis Mavrodakos, Konstantina Goggaki, and Polydoropoulos Konstantinos. In modern Olympic Games, the first substances used as reinforcement of the athlete for the coveted performance were heroin in racing and morphine on fights. Since then, there is a long history of doping in sport. In competitive sports, where main objective is the maximum athletic performance and, at all costs victory, growing number of athletes recourse to doping for strengthening capabilities, supplanting both moral inhibitions and the effects of this selection in their natural health and life achievements. This study just shows the moral evaluation of the use of illicit substances through the students 'views in the Sport Physical Education Department of the University of Athens. Students' views were recorded on a questionnaire. Their view is particularly important because of its modern and their future position in sport and education. The sample consisted of 200 students in Sport Physical Education Department of Athens, randomly selected. According to the survey results, the majority of the surveyed population had been suffering from the phenomenon of doping in sport. Men, in a small percentage, it seems to have more relaxed moral conscience regarding the use of doping substances by women. This may be due to the fact that in this sample, the men who are engaged to a greater extent with the high level championship.   Keywords: competitive sport, banned substances, ethics, use, questionnaire students. *** Απόσπασμα Έρευνας που διεξήχθη στο πλαίσιο της Γραμματείας Επιτροπής Ερευνών του Εθνικού και Καποδιστριακού Πανεπιστημίου Αθηνών με Επιστημονική Υπεύθυνη την Επίκουρη Καθηγήτρια Κων/να Γογγάκη και με θέμα: «Οι απόψεις των φοιτητών/τριών του ΤΕΦΑΑ Αθηνών σχετικά με τη χρήση, την πρόθεση χρήσης και τις ηθικές διαστάσεις της χρήσης των αναβολικών ουσιών στον αθλητισμό». Ηλεκτρονικό Περιοδικό ΠΕΠΦΑ<a style="font-size: initial; line-height: 1.5;" href="http://www.pepfa.gr/index.php?option=com_content&view=article&id=162:panagiotis-mavrodakos-konstantina-goggaki-polydoropoulos-konstantinos&catid=56:teyxos-2013&Itemid=54">http://www.pepfa.gr/index.php?option=com_content&view=article&id=162:panagiotis-mavrodakos-konstantina-goggaki-polydoropoulos-konstantinos&catid=56:teyxos-2013&Itemid=54 http://archive-gr.com/gr/p/pepfa.gr/2013-09-16_2866954-titles_6